PROPOSED IMPROVEMENTS TO FINISH THE DELAYED PROJECT OF PT ETS - Raditya Dwiprasta, Muhammad
PT ETS is a start-up that was previously engaged in the use and manufacture of drones which then shifted to engage in the Internet of Things (IoT) consulting. The latest project of PT ETS is a job given by PT XYZ to provide a system that can improve the traceability of the company's production system. However, the project has progress that is not by the plan and will certainly experience delays. Concerning the contract, the delay will certainly affect the income that ETS may get. This research was made to evaluate the project work carried out by ETS and provide solutions for project completion. The research uses the discussion method to obtain primary data and uses documents owned by ETS in the form of project contracts and other documentation to view the history of project work as secondary data. The two data are then used to analyze gaps in project work and project management, especially on schedule and cost. After knowing the gap that occurred, a search for the cause of the delay was carried out using the Fishbone Diagram. The causes of the problems found became the basis for developing solutions for ETS to complete the project. The solution is made using the Critical Path Method tool so that it can find out critical activities that can be given special treatment by ETS. Solutions are also made to improve project management. In this research, there is also an implementation explanation so that companies can easily implement the solutions provided